Positioning of corporate social responsibility in media reporting - Ahmad, Jamilah; Saad, Suriati (Routledge, Taylor & Francis Group, 2017)
Media has the capability to disseminate message and influence audience in developing perception, opinion or decision making. Media play an indispensable role in the dialogues around Corporate Social Responsibility (CSR). In addition to its function as an independent monitor for corporations media often act as a channel through which corporations communicate to the public. How media tell their stories about CSR have significant impacts on the public and policy makers expectations of companies and eventually influence the decision as of to what extent companies will conduct their business in a socially responsible manner. In order to understand how acceptance and behavior surrounding CSR develops, it is necessary to explore how the meaning and content of CSR are created. This article explores the CSR and media scenario in Malaysia. This article also examines how the media has framed and presented CSR for the period of one year (Jan 2013-Disember 2013). In these two top newspapers of English and Malay medium and the role of media setting for corporate CSR agenda. The findings confirms that media contributes to the construction of what CSR means in corporate practice by creating links between CSR and corporate activities; between CSR and media positioning; and between CSR and news value. These links create a notion of what CSR stands for and what it means in practice. Keywords: CSR Reporting, Media Positioning, Malaysia